Vascular Malformation Cases Profile in RSUP Dr. Kariadi Central-General Hospital Semarang Between 2020-2023 - Tan Margaretha Heidina Handoko; Najatullah Najatullah (Jurnal Plastik Rekonstruksi, 2025)
Introduction: Vascular malformations are abnormalities of the vascular system that arise from improper development during embryogenesis. These vascular anomalies are present at birth and grow proportionally to the size of the child. They have complex clinical presentations and are often misdiagnosed. There are few reports on epidemiology data of these anomalies, and this paper aim to contribute on vascular malformations descriptive epidemiological data.Method: Patients with vascular malformations who were registered in RSUP Dr. Kariadi Central-General Hospital between January 2020 and December 2023 were included in this paper. All data were collected retrospectively from medical records.Results: The gender distribution is dominated by male then followed female with the frequency of 51.2% and 48.8% subsequently. Age 1-20 years was the most dominant age range, contributing to 63.2% of the cases. The most commonly found type of vascular malformations are low-flow malformations with venous malformations (69.6%) being the most common and followed by lymphatic malformations (16%). Surgical treatment was done on 52% of the cases, followed by non-surgical (39.2%) and combination of both surgical and non-surgical methods (8.8%). The most common anatomical site was the craniofacial area (56.8%) followed by the limbs area (28.8%).Conclusion: Both diagnostic and therapy remain a challenge on vascular malformations. By fully understanding about these vascular anomalies, the proper diagnostic can be made hence the proper treatment.